Physico-chemical and microbial characteristics of banana (Musa sp.) leaf as a Philippine traditional packaging materials for Lye-treated boiled rice cake (Suman sa Lihiya) - Luna, Myrna Benita Z.
This study characterized the physico-chemical, and microbiological properties of banana leaf (BL) as raw, pre-treated, and processed leaves utilized for packaging of suman sa lihiya (SSL) prepared based on traditional knowledge. In Phase 1, traditional knowledge in BL harvesting and utilization as packaging material for SSL was documented through in-depth interview and field observation of actual processes. Moreover, relevant criteria used by SSL processors and BL providers in selecting BL for SSL processing were identified. Phase 2 involved characterization of the physico-chemical and microbiological properties of BL traditionally used as packaging for SSL. Also, physico-chemical and microbiological changes occurring in BL and SSL were monitored during storage. Finally, Phase 3 described the response of the key knowledge holders to feedback on laboratory derived results consolidated with traditional knowledge. In Phase 1, the knowledge holders identified were SSL processors in Cainta, Rizal and BL Providers in Batangas and Laguna. It was established that there are three varietal sources of BL including saba (Musa x paradisiaca L), butuan (Musa acuminata sbsp. errans), and lagkitan (Musa x paradisiaca L.). Among these, saba at leaf position 2 was commonly harvested by the BL providers. Traditional knowledge holders characterize BL for SSL in terms of color, maturity, half leaf dimensions, pliability, and cleanliness. Traditional knowledge holders shared varied traditional knowledge regarding leaf varietal sources and leaf maturity. Moreover, the packaging functions attributed by SSL for BL are communication, containment, protection, and sensory enhancement of SSL. In terms of leaf packaging material preparation, participating SSL processors clean visibly soiled leaf by wiping; and pre-treat BL by hot-ironing and steaming, to soften the leaf and facilitate folding. In Phase 2, it was established that in terms of half leaf dimensions, saba is considered the better leaf varietal source since it is wider, thicker, and bigger in leaf area. These findings supported traditional knowledge. Generally, butuan leaf had the highest tensile properties, lignin, wax, and acid insoluble ash which confer stability and structure to the material. Butuan and saba leaves had similar xxiv tensile properties whereas lagkitan had tensile properties less than saba. This was inconsistent with traditional knowledge that lagkitan is similar to saba and butuan is brittle compared to saba. It was established that within the grid-like structure of all three BL varietal sources there are smaller interconnected structures that possibly reinforce the mechanical strength of veins. The three BL varietal sources of banana raw material for packaging can be differentiated based on color analysis of both the top and bottom sides of the leaf. It was established that the top side color of saba is darker green in color relative to the two varieties. These findings were consistent with the traditional knowledge in sorting leaves as raw material for packaging. In terms of leaf maturity of saba leaf, it was established that the leaf position 0 had significantly weaker tensile properties than the mature leaves (leaf positions 1 to 3). This was consistent with traditional knowledge that leaf position 0 is fragile compared to the mature leaves. Moreover, it was observed that the tensile properties of the mature leaves were not significantly different from each other implying that aside from leaf position 2, leaf positions 1 and 3 may also be used for SSL. Generally, it was shown that lignin, wax, and acid insoluble ash increased with leaf age. Structurally, surface wax increased in size and density with leaf age. In terms of instrumental color properties, it was established that leaf position 0 was noticeably different from the mature leaves as it was lighter and more yellow. This indicated that in terms of color associated with SSL, leaf position 0 is not a good packaging material for SSL. In terms of leaf cleanliness, it was established that among the leaf varietal sources, butuan leaf had significantly higher number of filth and microbial load. Likewise, among the leaf positions studied, leaf position 1 had the highest number of filth because it was the least developed in vein density, wax, and lignin that confer protection to the leaf. Although BL was initially contaminated with filth and microorganisms, the thermal process that will be employed during SSL processing may improve its cleanliness. Laboratory-derived data pertaining to pre-treatment of BL were consistent with traditional knowledge that, generally, heat-treated leaves are more pliable than raw. Moreover, generally, it was xxv shown that hot-ironed leaf is a better pre-treatment process compared to steaming since the former had higher tensile properties. It was also shown the pre-treatment did not significantly improve the filth content and microbial properties of BL. Similarly, heat-treatment did not significantly affect the physico-chemical and microbiological properties of processed leaf. However, during storage, microbial load of processed leaf and SSL generally increased during storage. Furthermore, microbial load of processed SSL was generally higher than the leaf. This may be attributed to the saccharolytic nature of the product which is more conducive for microbial growth than the leaf that is mainly lignocellulosic. Phase 3 established that traditional knowledge holders have various suggestions to improve their practices in BL harvesting, leaf preparation and pre-treatment, SSL processing, and packaging. However, limitation in resources was cited as the major hindrance for compliance. This study demonstrated there are some aspects of traditional knowledge in the utilization of banana leaf as packaging for SSL and harvesting that are supported by laboratory-derived data generated using the tools of food science and technology. This may be due to the differences in the sensitivity of the methods used in the two knowledge systems. It is recommended that the actual performance of butuan and leaf positions 1 and 3 as packaging materials for SSL be evaluated. Furthermore, standards for BL in terms of raw material properties, harvesting and preparation methods should be established as BL is a food contact material that would influence the quality and safety of indigenous food products.